Myth and meaning - Lévi-Strauss, Claude (Routledge, 1979)
In addresses written for a wide general audience, one of the twentieth century's most prominent thinkers, Claude Levi-Strauss, here offers the insights of a lifetime on the crucial questions of human existence. Responding to questions as varied as 'Can there be meaning in chaos?', 'What can science learn from myth?' and 'What is structuralism?', Levi-Strauss presents, in clear, precise language, essential guidance for those who want to learn more about the potential of the human mind.